Miscarriage of Justice and Backlog of Criminal Cases: A Case Study of Punjab Pakistan’s Courts From (January 01, 2022 To December 31, 2022) - Ghani, Abdullah; Ayub, Zainal Amin; Mat Rus, Mukhriz (Society of Cultural Studies and Social Sciences, Hong Kong, 2023)
Miscarriage of Justice means returning an unfair verdict based on the evidence presented as a legal justice failure. This process includes investigation, prosecution and trial. The data for the present study has been collected from the office of Punjab Prosecution Lahore. The time span for data collections ranges from January 01, 2022 to December 31, 2022. The categories of the cases which have been dealt in the present study about miscarriage of justice include, kidnapping, abduction to murder, to confine a person, dacoity, Robbery, theft, Murder cases (u/s 322), fear of injury in order to commit extortion and putting a person in fear of death to commit extortion. The present research employs the theoretical frame work which states that “A grossly unfair outcome in a judicial proceeding, as when a defendant is convicted despite a lack of evidence on essential element of the crime” and “an error made in a court of law that results in an innocent person being punished or a guilty person being free”. The analysis of the data reveals that the percentage of miscarriages of justice from the courts related to kidnapping is 0.43%, abduction to murder is 0.00%, to confine person is 0.11%, dacoity 1.08%, robbery 2.99%, theft related cases is 0.29%, criminal breach of trust is 0.48%, murder cases (u/s 322) is 1.82%, extortion is 0.00 % and putting person in fear of death of grievous hurry in order to commit extortion is 0.00%. The study recommends that until the hurdles involved in the process of investigation, prosecution and trial are removed and this complete process is made effective and up dated, the percentage of miscarriage of cases cannot be improved. In this regard, police, prosecution and courts must introduce reforms in their respective domains